Driving method of interior permanent magnet synchronous motor for railroad cars using a synchronous PWM method - Bak, Yeongsu; Lee, June Seok; Lee, Kyo Beum (Journal of the Korean Society for Railway, 2019)
This paper presents a driving method for an interior permanent magnet synchronous motor (IPMSM) for railroad cars using a synchronous PWM method. Since the fundamental frequency of an inverter is increased in the high-speed region of the IPMSM for railroad cars, it occurs that the number of switching pulses of the inverter decreases during one period of the fundamental waveform. In this case, the problem of an unbalanced output voltage can occur due to the asynchronous nature of the fundamental and carrier waveform; a synchronous PWM method is used to overcome the problem. In addition, flux weakening control is required to drive the IPMSM at higher speed than the base speed of the IPMSM. However, if reference currents are changed for flux weakening control, the synchronous PWM method cannot be performed properly. In this paper, a driving method of the IPMSM for railroad cars using the synchronous PWM method in the flux weakening region is proposed. The effectiveness of the proposed method is verified by simulation results.
Keywords: Constant power region; Flux weakening control; IPMSM; Synchronous PWM method